Analysis of the Causes of Duplicate Medical Records in the Health Recording System at the South Ponorogo Community Health Center Registration Desk - Hino Marga Yasa; Rumpiati Rumpiati (Institut Kesehatan Pelamonia, 2025)
Hino Marga Yasa, 2024